Uso de filtración por membrana para la recuperación de Campylobacter de muestras de pollo crudo provenientes de supermercados locales en Culiacán, Sinaloa, México - Soto-Beltrán, J. M.; Quiñones, B.; Ibarra-Rodríguez, A.; Amézquita-López, B. A. (Revista Bio Ciencias, 2019)
Campylobacter jejuni and Campylobacter coli are responsible for human gastroenteritis worldwide, and the consumption of raw and undercooked poultry contributes to human infections. The present study examined the presence of C. jejuni and C. coli from retail chicken carcasses, purchased from local markets in the Culiacan Municipality in Sinaloa, Mexico. To improve the recovery of Campylobacter, the package liquid from the raw chicken carcasses was subjected to membrane filtration after an overnight enrichment under microaerophilic conditions. The presence of C. jejuni and C. coli was further determined by PCR amplification of the lpxA gene. Presumptive Campylobacter colonies were recovered from 56.7% (17/30) of the chicken carcasses purchased from 63.6% (7/11) of the retail markets examined. Genotyping assays detected C. jejuni in 33.3% (10/30) of the carcasses examined. This study identified for the first time C. jejuni in raw chicken carcasses in Northwestern Mexico and provided valuable information for monitoring Campylobacterin retail meats.